Introduction - AABFJ Financial Planning Special Issue 2009 - Ciorstan J. Smark; B. Murphy; S. Taylor (Australasian Accounting, Business and Finance Journal, 2009)
This special issue draws on recent work of financial planning specialists, finance specialists and economists to document some of the trends, perception and challenges of financial planning in 2009. This diversity of contributors reflects the diversity and the multiplicity of influences that impact on financial planning.